Effect of Blood Pressure on Spirometer Variables in Undergraduate Students of a Medical College in North-East India (GAIMS Journal of Medical Sciences, 2026)
Background: Medicos must be physically fit before serving patients. Blood pressure and Spirometer variables are essential markers of health status of an individual. . Our study aims at determining the effect of Blood Pressure on Pulmonary parameters of medical students to identify the Risk Groups who are prone to develop Hypertension and to provide recommendations. Material and methods: Students were classified on the basis of BP (viz. Normotensive, Hypertensive). Spirometric variables viz. FVC, FEV1, PEFR of the students were recorded and compared between the hypotensives, normotensives and hypertensive students. The response frequencies and descriptive statistics like mean and standard deviations were calculated. In case of more than two variables, P values were calculated using ANOVA test by Interactive statistics software. The P value